Zollinger-Ellison Syndrome: Intermittent Diarrhea, Relentless Hypokalemia, and Hypergastrinemia - Chishoim, Joseph C. (1981)
A case of hypergastrinemia, diarrhea, and relentless hypokalemia occurring in a middleaged, mildly hypertensive female is described. The presence of a gastrinoma was suggested by the additional findings of an inordinate degree of hypokalemia for the amount of thiazide used for the treatment of her hypertension; failure of her hypokalemia to correct itself with adequate doses of oral potassium that had previously corrected this problem; and amelioration of her symptoms and hypokalemia when she was treated with short-term oral potassium chloride and longterm cimetidine.